Where did the eastern Mayas go? The historical, relational, and contingent interplay of Ch'orti' indigeneity - Metz, Brent E., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2022)
This volume explores the issue of who is Indigenous by focusing on the sociohistorical transformations over the past two millennia of the Ch'orti' Maya. The language of elite writers in Classic Maya civilization was Proto-Ch'olan, but by the end of the colonial period (1524-1821) few Ch'orti' speakers remained.--Provided by publisher.
Four approaches to indigeneity -- Exploring the precolonial foundations of the "Ch'orti' Area" -- Colonial predation and Apay division and contraction -- Indigeneity in the last Ch'orti'-speaking municipios of Guatemala: Jocotán, Olopa, Camotán, San Juan Ermita, La Unión -- Beyond the contemporary Ch'orti'-speaking area of Guatemala -- History behind the Honduran Chorti movement -- Survey of Copán Ruinas, Santa Rita, Cabañas, and El Paraíso -- Ocotepque: Indians, Ch'orti', Indigenous, or Mestizos? -- Northwestern, El Salvador: Can indigeneity disappear? -- Conclusion: Who's indigenous Ch'orti'? Who Cares?
Keywords: Chorti Indians -- History; Chorti language -- Guatemala; Chorti language -- Honduras; Chorti Indians -- Ethnic identity; Chorti Indians -- Social conditions